Conscience and conversion : religious liberty in post-revolutionary France - Kselman, Thomas A. (Thomas Albert), 1948- (Yale University Press, 2018)
Religious liberty is usually examined within a larger discussion of church-state relations, but Thomas Kselman looks at several individuals in Restoration France whose high-profile conversions fascinated their contemporaries. Exploring their reasons and the repercussions they faced, Kselman demonstrates how this expanded sense of liberty informs our secular age. --! From back cover.